A hybrid approach for character modeling using geometric primitives and shape-from-shading algorithm. Issue 2 (6th November 2015) - Kazmi, Ismail Khalid; You, Lihua; Zhang, Jian Jun
Abstract: Organic modeling of 3D characters is a challenging task when it comes to correctly modeling the anatomy of the human body. Most sketch based modeling tools available today for modeling organic models (humans, animals, creatures etc) are focused towards modeling base mesh models only and provide little or no support to add details to the base mesh. We propose a hybrid approach which combines geometrical primitives such as generalized cylinders and cube with Shape-from-Shading (SFS) algorithms to create plausible human character models from sketches. The results show that an artist can quickly create detailed character models from sketches by using this hybrid approach.